2023
DOI: 10.3390/ph16121636
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition, Mineral Profiling, In Vitro Antioxidant, Antibacterial and Enzyme Inhibitory Properties of Selected Indian Guava Cultivars Leaf Extract

Moses Sam Arul Raj,
Singamoorthy Amalraj,
Saud Alarifi
et al.

Abstract: Psidium guajava L. is a small evergreen tree known for its magnificent medicinal and nutritional value. This study aimed to evaluate the nutritional profile and in vitro pharmacological potentialities of the different leaf extracts of four cultivars of Psidium guajava namely Surka chitti, Allahabad safeda, Karela, and Lucknow-49. The standard procedures of the Association of Official Analytical Chemists (AOAC) were followed to carry out the nutritional analysis and all of the cultivars recorded the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This study once again confirmed the repellent effect of PG OE on D. citri. PG is rich in various vitamins, such as vitamin C, and mineral elements, which can effectively promote the synthesis of nitric oxide in the human body, and has the effects of dilating blood vessels and lowering blood pressure [48,49]. The high content of β-caryophyllene in PG leaves can also be used as a pest repellent and attractant in agricultural pest control.…”
Section: Discussionmentioning
confidence: 99%
“…This study once again confirmed the repellent effect of PG OE on D. citri. PG is rich in various vitamins, such as vitamin C, and mineral elements, which can effectively promote the synthesis of nitric oxide in the human body, and has the effects of dilating blood vessels and lowering blood pressure [48,49]. The high content of β-caryophyllene in PG leaves can also be used as a pest repellent and attractant in agricultural pest control.…”
Section: Discussionmentioning
confidence: 99%